STRATEGI PENERAPAN SALURAN DISTRIBUSI UMKM DI TANGERANG DALAM MENGHADAPI PERSAINGAN - Rizka Indah Mardianti (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This research was conducted to find out how the selection of distribution channels used in one of SMEs in the Tangerang area in marketing their products so that the product quickly reaches the hands of consumers, and to know how the functions in the distribution channels carried out by MSMEs through the application of Multi-Channel Marketing channels. The number of informants of this study is as many as 3 people consisting of Owner, Marketing, SPG, to 3. The method used is qualitative which is descriptive. The research sample used is purposive sampling. Based on the results of the study, that the selection of distribution channels used is a direct-distribution channel and indirect distribution channels where SMEs not only market their products directly to consumers and but also market their products through intermediaries, such intermediaries are resellers located in all regions that already have cooperation with SMEs, and for the functions of distribution channels carried out by SMEs are carried out well and in accordance with the procedure.